Fluxos de tecidos foliares, características morfogênicas e estruturais do azevém pastejado por bezerras de corte recebendo suplemento - Ribeiro, Laila Arruda (2012)
The experiment was carried out at the Department of Animal Science, UFSM in the period from July to October 2009. Morphogenetic and structural characteristics of Italian ryegrass (Lolium multiflorum Lam) under grazing beef heifers in exclusively ryegrass pasture or receiving fat extruded (0.20% of body weight (BW) and corn grain (0.78% of BW) were studied. The supplement was given daily at 14 hours. The grazing method was continuous stocking with variable number of animals to keep the forage mass in 1500 kg/ha of dry matter. Were taken morphogenetic and structural measures using marked tiller to determine the flow of leaf tissues of ryegrass. The experimental design was completely randomized in a repeated measures over time with three treatments and two area replications. The data were submitted to ANOVA, Tukey test and regression analysis according to the days of evalution. Analyses were performed using the statistical program SAS 9.0 (2006). Flows of leaf tissues were similar for the different alternatives to supplement and changed throughout the phenological Italian ryegrass cycle. Consumption of leaf blades is similar for beef heifers receiving supplement or exclusively on grazing and it is varies during the use of the pasture. The intensity and frequency of defoliation and the morphogenesis of Italian ryegrass are not modified by supplement to grazing animals. Changes in morphogenesis are dependent with the development of the Italian ryegrass cycle. The intensity of defoliation increase daily for a frequency of defoliation that varies throughout Italian ryegrass cycle of use.